Mitigation of Primary Graft Dysfunction in Lung Transplantation: Current Understanding and Hopes for the Future. (March 2020) - Wilkey, Barbara J.; Abrams, Benjamin A.
Primary graft dysfunction (PGD) is a form of acute lung injury that develops within the first 72 hours after lung transplantation. The overall incidence of PGD is estimated to be around 30%, and the 30-day mortality for grade 3 PGD around 36%. PGD is also associated with the development of bronchiolitis obliterans syndrome, a specific form of chronic lung allograft dysfunction. In this article, we will discuss perioperative strategies for PGD prevention as well as possible future avenues for prevention and treatment.